When "different" means "worse": In-group prototypicality in changing intergroup contexts - Waldzus, S. (2019)
An experiment with 213 participants provided evidence for in-group projection—the generalization of distinctive in-group attributes to a superordinate category. The frame of reference for in-group (German) judgments was manipulated by presenting either Italians or the British as an out-group. Results showed that attributes on which Germans differed from each out-group were accentuated not only in in-group judgments but also when judging Europeans. By adapting features of the superordinate category to those of the in-group, the in-group's similarity to, and the out-group's deviation from, the prototype of the superordinate category were maintained, if not emphasized. Further, higher in-group prototypicality—compared to out-group prototypicality—for the superordinate category was related to negative out-group attitudes. In-group projection was reduced when a complex representation of the superordinate category was primed.